(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The current research work covers the diversity of freeliving ciliated protzoa from freshwater bodies of Pravara river Ahmednagar regions in Maharashtra (India). During this study, a total of 7 species of ciliates recorded, Paramecium caudatum, Paramecium multimicronucleatum, Paramecium etraurelia,Vorticella companula, Stenor polymorphus, Euplotes eurystomus, Stylonychia mytilus, from pravara river Ahmednagar. The identification has been made mainly on the basis of body shape, size, arrangements of cilia, and structure of macro- and micronucleus.